A pilot randomized trial comparing face-to-face and internet-based unified transdiagnostic treatment for adolescents with anxiety and depressive disorders in Iran - Mousavi, Nasim; Momeni, Fereshteh; Pourshahbaz, Abbas; Poursharifi, Hamid; Daneshian, Zahra; Andersson, Gerhard (Frontiers in Psychiatry, 2025)
ObjectiveThe use of internet-based treatments has increased significantly in recent years. As remote technologies continue to evolve, psychotherapy research is progressively shifting toward these approaches. Anxiety and depressive disorders are highly prevalent in adolescents, imposing significant personal and societal costs. Identifying effective and scalable treatments for this age group is therefore essential. This study aimed to compare the efficacy of face-to-face and internet-based unified transdiagnostic treatment in reducing symptoms and improving functioning in adolescents with anxiety and depressive disorders.MethodsA pilot randomized controlled trial (RCT) with pre-test, post-test, and follow-up assessments was conducted to compare the efficacy of face-to-face and internet-based treatments. Forty-nine adolescents (aged 13–18 years) from Tehran, Alborz, Gilan, and Kerman were randomly assigned to one of three groups: face-to-face treatment, internet-based treatment, or a control group. Assessments were conducted before treatment, after treatment, and at six months post-treatment. A Mixed-model Analysis of Variance was used for data analysis.ResultsBoth face-to-face and internet-based transdiagnostic treatments demonstrated similar efficacy in reducing anxiety and depression symptoms, improving functioning, decreasing negative affect, and reducing avoidance in adolescents. However, neither treatment significantly improved positive affect or distress tolerance. Additionally, the effects in the internet-based group were maintained through the follow-up phase, while the face-to-face treatment group did not sustain these results by the six-month follow-up.ConclusionBased on the results of this study, internet-based transdiagnostic treatment is also a viable option for treating anxiety and depressive disorders. The large scale implementation of internet-based transdiagnostic psychotherapy could be an effective strategy to bridge the significant gap between adolescents’ mental health needs and the availability of evidence-based treatments for anxiety and depression.Clinical trial registrationhttps://irct.behdasht.gov.ir/trial/62220, identifier IRCT20220226054129N1.